The Unique Way Balinese Medicine Works To Achieve Well-Being - Ni Kadek Meri Wahyuni; Ni Made Swasti Wulanyani (Indonesian Scientific Publication, 2023)
Everyone always expects health, and this is one of the indications that individuals have good well-being. Treatment is one of the efforts to be able to restore individual health. There are two types of treatment, namely medical and traditional treatment. Balinese people do not only medical treatment but also traditional treatment known as Balian treatment. The study aimed to determine the process of health-seeking behavior of Balinese people who switch from medical treatment to Balian treatment. The research method is descriptive qualitative, using five respondents selected through purposive sampling. The results of this study indicate that the causes of individuals who switch medical treatment to Balian treatment in Bali are dissatisfaction with the results of medical treatment, the influence of significant others, individual beliefs and perceptions of Balian practices, and cultural traditions. The primary purpose of Balinese people switching from medical treatment to Balian treatment is to get healing as a unique effort to achieve well-being.